Bridging the Gap for Malay Literature Content on Built Environment Through Wiki as A Collaborative Writing Tool - Asif, Nayeem; Utaberta, Nangkula; Bin Sabil, Azmal (International Journal of Engineering and Technology, 2019)
This paper describes the procedure of engaging students in producing collaborative writing and utilizing online platform to build up a database of written content on specific discipline using the student generated writings. The aim is to add up to the content on built environment in Malay language as professional and academicians reports a scarcity in this field. The process involves thirty three third year students of architecture as the primary participants to produce writings based on a given template and three post graduate students to review and comment on the writings for maintaining a standard quality. 24 articles were selected after the screening process and uploaded to a wiki platform named Wikia under the title of WARIS ARKIEDIA. Continuation of this process with additional bathes of student can add up more articles in the existing database. It is expected that, once available online, users participation can effectively improve the content quality as well as add on more related wikis and contribute to build up a national architecture literature database in Malay language.Â Â